2019
DOI: 10.5194/acp-19-15-2019
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of temperature and precipitation in the Indian Jammu and Kashmir region for the 1980–2016 period: implications for remote influence and extreme events

Abstract: Abstract. The local weather and climate of the Himalayas are sensitive and interlinked with global-scale changes in climate, as the hydrology of this region is mainly governed by snow and glaciers. There are clear and strong indicators of climate change reported for the Himalayas, particularly the Jammu and Kashmir region situated in the western Himalayas. In this study, using observational data, detailed characteristics of long- and short-term as well as localized variations in temperature and precipitation a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(40 citation statements)
references
References 99 publications
6
29
0
Order By: Relevance
“…In Himalayan mountains, different trends have been observed in precipitation over recent decades (IPCC, 2001). While some studies (Shrestha, 2000;Borgaonkar and Pant, 2001) observed increasing precipitation, others reported a decreasing precipitation trend (Kumar and Jain, 2010;Dimri and Dash, 2012;Zaz et al, 2019). The present study found higher warming and decreasing precipitation trends in winter and spring months, which is consistent with other studies carried out both in the same region (Zaz et al, 2019) and in other parts of Himalaya (Archer and Fowler, 2004).…”
Section: Patterns Of Climate Changesupporting
confidence: 91%
See 2 more Smart Citations
“…In Himalayan mountains, different trends have been observed in precipitation over recent decades (IPCC, 2001). While some studies (Shrestha, 2000;Borgaonkar and Pant, 2001) observed increasing precipitation, others reported a decreasing precipitation trend (Kumar and Jain, 2010;Dimri and Dash, 2012;Zaz et al, 2019). The present study found higher warming and decreasing precipitation trends in winter and spring months, which is consistent with other studies carried out both in the same region (Zaz et al, 2019) and in other parts of Himalaya (Archer and Fowler, 2004).…”
Section: Patterns Of Climate Changesupporting
confidence: 91%
“…Based on the in situ data recorded during the present study, increase in mean annual temperature, and a decrease in precipitation was clearly observed. An almost similar trend was reported in the analysis of historical climate data by Zaz et al (2019) in this Himalayan region. In Himalayan mountains, different trends have been observed in precipitation over recent decades (IPCC, 2001).…”
Section: Patterns Of Climate Changesupporting
confidence: 87%
See 1 more Smart Citation
“…The analysis of the snout retreat of all the four parts of Kolahoi Glacier also indicated an accelerated retreat of the glacier across the analysis period. This could perhaps be attributed to the warming environment that increases ablation and [77,78] forces change in the form of precipitation [21,31,79] and potentially high ambient black carbon concentration, such as that observed near glaciers in the Kashmir region [80,81]. The accelerated rate of retreat of glaciers in northwest Himalaya has been very well documented in many recent studies [82][83][84].…”
Section: Discussionmentioning
confidence: 98%
“…Variations in precipitation and temperature within the valley are mainly the result of altitude and aspect. Meteorological data shows that the annual temperature in the Kashmir Valley varies from -10 to 35 • C (Zaz et al, 2019).…”
Section: Climate and Its Evolutionmentioning
confidence: 99%